Calibration method for attenuator piece used in calibrating a transmittance visibility meter. Issue 23 (29th November 2019) - Liang, Jing; Zhang, Guoyu; Zhang, Jian; Xu, Da; Sun, Gaofei
Abstract : Aiming at the method of indoor calibration of a transmission visibility meter has not been established; a new calibration method by measuring the luminous transmittance of attenuator piece was established. Based on the high homogeneity stability lighting and the multi‐spectral transmittance analysis technique, a calibration system of the transmission visibility meter by measuring the luminous transmittance of the attenuator piece was designed. The experiment was designed by measuring the luminous transmittance with the range of 0.2–99.2% of a series of calibrated attenuators and the visibility in the range of 40 m to 20 km, then the luminous transmittance errors, the meteorological optical range (MOR) errors and their uncertainty were obtained. The result showed that the luminous transmission error was within ±0.18%, which satisfied the calibration requirement for transmission visibility meter transmittance; the MOR calibration error met the accuracy requirements of the International Civil Aviation Organisation for visibility measurement; this work will have guiding significance in establishing a calibration procedure for the transmission visibility meter.